PENGETAHUAN TENTANG VAKSINASI COVID-19 DENGAN KEIKUTSERTAAN IBU HAMIL DALAM PROGRAM VAKSINASI DI PUSKESMAS BANGSAL KECAMATAN BANGSAL KABUPATEN MOJOKERTO - Sri Wardini Puji Lestari; Zulfa Rufaida (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
COVID-19 or also known as the Novel Coronavirus that caused an outbreak of pneumonia in the city of Wuhan, China in December 2019 and spread to other countries starting January 2020. Indonesia itself announced a case of covid 19 from March 2020. Pregnant women have an increased risk of getting severe if infected with covid -19, especially in pregnant women with certain medical conditions. The purpose of this study was to determine the relationship between knowledge about vaccination and the participation of pregnant women in the vaccination program. Analytical research method, the variables used are knowledge about vaccination and the participation of pregnant women in the vaccination program population method is pregnant women who visit the Puskesmas Bangsal Kec. Ward Kab. Mojokerto, a sample of 30 respondents instrument research using questionnaires, data analysis with chi square statistical test. The results showed that respondents' knowledge about vaccination was in the good category 26 (86.6%) and respondents who participated in the vaccination program were 24 (80%). Knowledge analysis with participation in vaccination program Knowledge with participation in vaccination Respondents with good knowledge as many as 24 (92.3%) participated in the vaccination program. The results of the chi square test obtained a p value of 0.000 with an alpha value of 0.05, with the conclusion that there was a close relationship between knowledge and participation in the COVID-19 vaccine. The conclusion of this study is that there is a close relationship between knowledge and participation in the COVID-19 vaccine. It is hoped that health workers will always socialize the covid-19 vaccination program, especially for pregnant women.